2019
DOI: 10.47108/jidhealth.vol2.iss1.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of malnutrition among the internally - displaced old age people in the Tikrit City, Iraq

Abstract: Background: With the steady increase in the number of old age people, the prevalence of chronic diseases, and the health expenditures, the importance of preventing malnutrition is becoming more critical than ever. This study aimed to assess malnutrition among the internally- displaced old age people in Iraq. Methods: A descriptive cross-sectional study conducted between November 2016 and March 2017 at the Dream city camp for the internally - displaced persons in Tikrit city, Iraq. Data was collected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…38 There is also worrying evidence that older adults residing in regions with deteriorating security situations face high food insecurity. 41 The COVID-19 pandemic intensified food insecurity globally, with panic buying and food hoarding leading to price hikes and food shortages. 42,43 Older populations, particularly those with comorbidities or without social support systems, often could not access food supplies that were in shortage.…”
Section: Food Insecuritymentioning
confidence: 99%
“…38 There is also worrying evidence that older adults residing in regions with deteriorating security situations face high food insecurity. 41 The COVID-19 pandemic intensified food insecurity globally, with panic buying and food hoarding leading to price hikes and food shortages. 42,43 Older populations, particularly those with comorbidities or without social support systems, often could not access food supplies that were in shortage.…”
Section: Food Insecuritymentioning
confidence: 99%
“…The potential reasons for higher prevalence of malnutrition among children were majorly being on crucial life period requiring quality full nutrient for body and mental growth, reduced adaptive response to hunger and unable to stand by themselves as an autonomous for their nutritional requirement and care [22,23]. Previous studies have also shown that IDPs and refugees were at high risk of developing malnutrition through recent devastated increment of man-made and natural disasters [24,25].…”
Section: Associated Factors Of Nutritional Status Among Study Partici...mentioning
confidence: 99%
“…The Iraqi family is distinguished by the number of its members and its close association with the restoration of society [1]. However, the rapid developments in technology, accelerated lifestyle changes, successive wars, displacement, malnutrition, unsafe drinking water, and poor medical and healthcare services Were existential challenges that led to the restructuring of the family entity, such as the early separation of children from the family and appearance of single-head families [2,3,4]. United Nations Development Program (UNDP) reported in 2013 that for every ten Iraqi families, one family is headed by the female gender [5].…”
Section: Introductionmentioning
confidence: 99%